Genetic variations in detoxification enzymes and HIF‐1α in Japanese patients with COPD. (6th July 2011) - Putra, Andika Chandra; Tanimoto, Keiji; Arifin, Marina; Antariksa, Budhi; Hiyama, Keiko
Abstract Introduction: Genetic factors contribute as major determinants in the pathophysiological mechanisms of chronic obstructive pulmonary disease (COPD). Therefore, identification of candidate genes and various gene polymorphisms have improved our understanding of COPD. Objectives: Clarify the genes, including HIF1A, that contribute to the development of COPD. Methods: We compared the genotype frequencies of 12 polymorphisms in seven detoxification‐related genes (GSTM1, GSTT1, GSTP1 exon 5, CYP1A1 exon 7, CYP1A1 3′‐flanking, CYP2E1 intron 6, CYP2E1 5′‐flanking, EPHX1 exon 3, EPHX1 exon 4 and HMOX1 promoter) and the hypoxia‐related HIF1A (C1772T and G1790A) genes between 48 Japanese patients with work‐related COPD who had a working history in a poison gas factory during World War II and two control groups (n = 172 and 110 subjects, respectively). Results: As expected, wild homozygotes for GSTP1 Ile105Val and EPHX1 slow/very slow phenotypes were associated with susceptibility (P = 0.031) and severity (P = 0.036) of COPD, respectively. Moreover, compound heterozygosity of transcription‐activating HIF1A polymorphisms was observed in two patients with COPD, but not in control individuals (P = 0.091). Conclusion: This is the first report that examined HIF1A polymorphisms in COPD and demonstrated a possible role of HIF‐1α in COPD, as well as GSTP1 and EPHX1. Please cite this paper as: Putra AC, Tanimoto K, Arifin M, Antariksa B and Hiyama K. Genetic variations in detoxification enzymes and HIF‐1α in Japanese patients with COPD. Clin Respir J 2013; 7: 7–15.